Metal-induced reductive ring opening of 1,2,4,5-tetrazines: Three resulting coordination alternatives, including the new non-innocent 1,2-diiminohydrazido(2-) bridging ligand system - Maji, Somnath; Sarkar, B.; Patra, S.; Fiedler, Jan; Mobin, Shaikh M.; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Inorganic Chemistry, 2006)
{Reaction of 3,6-diaryl-1,2,4,5-tetrazines (aryl = R = phenyl, 2-furyl or 2-thienyl) with 2 equiv of Ru(acac)(2)(CH3-CN)(2) results in reductive tetrazine ring opening to yield diruthenium complexes [
Keywords: crystal engineering; hydrogen bonds; molecular; recocynition; Self-assembly; supramolecular chemistry

Valence-state analysis through spectroelectrochemistry in a series of quinonoid-bridged diruthenium complexes [(acac)(2)Ru(mu-L)Ru(acac)(2)](n) (n =+2,+1, 0,-1,-2) - Ghumaan, Sandeep; Sarkar, Biprajit; Maji, Somnath; Puranik, Vedavati G.; Fiedler, Jan; Urbanos, Francisco A.; Jimenez-Aparicio, Reyes; Kaim, Wolfgang; Lahiri, Goutam Kumar (Chemistry-A European Journal, 2008)
The quinonoid ligand-bridged diruthenium compounds [(acac)(2)Ru(mu-L2-)Ru(acac)(2)] (acac(-) = acetylacetonato = 2,4-pentanedionato; L2- = 2,5-dioxido-1,4-benzoquinone, 1; 3,6-dichloro-2,5-dioxido-1,4-benzoquinone, 2; 5,8-dioxido-1,4-naphthoquinone, 3; 2-3-dichloro-5,8-dioxido-1,4-naphthoquinone, 4; 1,5-dioxido-9,10-anthraquinone, 5; and 1,5-diimido-9,10-anthraquinone, 6) were prepared and characterized analytically. The crystal structure analysis of 5 in the rac configuration reveals two tris(2,4-pentanedionato)ruthenium moieties with an extended anthracenedione-derived bis(ketoenolatee) pi-conjugated bridging ligand. The weakly antiferro-magnetically coupled {Ru-III(mu-L2-)Ru–(III)} configuration in 1-6 exhibits complicated overall magnetic and EPR responses,. ne simultaneous presence of highly redox-active quinonoid-bridging ligands and of two ruthenium centers capable of adopting the oxidation states +2, +3, and +4 creates a large variety of possible oxidation state combinations. Accordingly. the complexes 1-6 exhibit two reversible one-electron oxidation steps and at least two reversible reduction processes. Shifts to positive potentials were observed on introduction of Cl substituents (1 -> 2, 3 -> 4) or through replacement of NH by O (6 -> 5). The ligand-to-metal charge transfer (LMCT) absorptions in the visible region of the neutral molecules become more intense and shifted to lower energies on stepwise reduction with two electrons. On oxidation, the para-substituted systems 1-4 exhibit monocation intermediates with intervalence charge transfer (IVCT) transitions of (RuRuIV)-Ru-III mixed-valent species. In contrast, the differently substituted systems 5 and 6 show no such near infrared (NIR) absorption. While the first reduction steps are thus assigned to largely ligand-centered processes, the oxidation appears to involve metal-ligand delocalized molecular orbitals with variable degrees of mixing.
Keywords: magnetic properties; quinones; ruthenium; spectroelectrochemistry; structure elucidation; valence-state distributions